Human POT1 unfolds G-quadruplexes by conformational selection - Chaires, Jonathan B (Nucleic Acids Res, 2020)
The reaction mechanism by which the shelterin protein POT1 (Protection of Telomeres 1) unfolds human telomeric G-quadruplex structures is not fully understood. We report here kinetic, thermodynamic, hydrodynamic and computational studies that show that a conformational selection mechanism, in which POT1 binding is coupled to an obligatory unfolding reaction, is the most plausible mechanism. Stopped-flow kinetic and spectroscopic titration studies, along with isothermal calorimetry, were used to show that binding of the single-strand oligonucleotide d[TTAGGGTTAG] to POT1 is both fast (80 ms) and strong (−10.1 ± 0.3 kcal mol(−1)). In sharp contrast, kinetic studies showed the binding of POT1 to an initially folded 24 nt G-quadruplex structure is four orders of magnitude slower. Fluorescence, circular dichroism and analytical ultracentrifugation studies showed that POT1 binding is coupled to quadruplex unfolding, with a final complex with a stoichiometry of 2 POT1 per 24 nt DNA. The binding isotherm for the POT1-quadruplex interaction was sigmoidal, indicative of a complex reaction. A conformational selection model that includes equilibrium constants for both G-quadruplex unfolding and POT1 binding to the resultant single-strand provided an excellent quantitative fit to the experimental binding data. POT1 unfolded and bound to any conformational form of human telomeric G-quadruplex (antiparallel, hybrid, parallel monomers or a 48 nt sequence with two contiguous quadruplexes), but did not avidly interact with duplex DNA or with other G-quadruplex structures. Finally, molecular dynamics simulations provided a detailed structural model of a 2:1 POT1:DNA complex that is fully consistent with experimental biophysical results.